Migration of radiocaesium in six Swedish pasture soils after the Chernobyl accident - Persson, Henning (2008)
This study comprises six pasture soils in central and northern Sweden which were strongly affected by the Chernobyl fallout in 1986. The aim of the study was to investigate the vertical migration and plant uptake of radiocaesium as related to soil texture and other soil properties. The results were compared with earlier studies made on the same sites in 1987 to 2005. The soils were sampled down to 60 centimetres depth and analysed in layers. 21 years after the accident the main part of the activity (61-97 %) was still present in the upper ten centimetres of the soil. The migration rate as a whole decreased during the sampling period but varied considerably between the sampling occasions at each location. The mean migration rates were in the range of 0.2-0.5 cm year-1. There is a clear decrease in plant uptake with time, the decrease was however greatest in the first years after fallout. In 2007 the transfer of 137Cs to the vegetation was highest in an organic soil and in a gravely sandy loam in the mountain region and lowest in a clay soil. In this study there was no clear connection between migration and soil properties 21 years after the accident. Instead the differences in migration seam to be a product of biological and hydrological factors at the individual locations.